Alfabetizar em contextos de cibercultura - Moura, Elizangela silva de Sousa (Universidade Federal do Tocantins, 2020)
Nowadays, in order to be considered literate, it is necessary to go beyond the acquisition and decoding of signs, since current society presents a high technological advance, increased information and access to information and communication technologies, which makes it urgent and necessary for the individual to master the different codes of the various languages present in contemporary society and in times of cybercrime and cyberspace. The reflection on this context brought the preoccupation that led to the development of this research, whose results are presented in this Dissertation. The general objective of this research was to identify the perception of the literacy teachers of Santa Cruz Elementary School in Araguaína / TO in regarding to the use of digital media in the literacy process. And, more specifically, present a technical production, which consists of a didactic sequence of literacy practices associated with digital media icons. The approach had taken in the research was qualitative, with field research procedures, whose instrument of data collection was the semi-structured interview. The research revealed that teachers understand the importance of integrating digital media into literacy practice and recognize that they can not ignore that children coexist with a computerized reality, however, also revealed that in their practices teachers have little ownership of digital technologies .